An investigation into linguistic features of simile and repetition in "Wuthering Heights" by Emily Bronté and its Vietnamese translational version - Ngụy, Như Phương Dung. (The University of Da Nang, 2014)
The thesis is conducted to investigate the linguistic features of simile and repetition in “Wuthering Heights” by Emily Bronté and its Vietnamese translational version. The study aims at finding out similarities and differences of these two devices in English and Vietnamese. The samples under investigation are words, phrases and sentences containing simile and repetition collected in the original novel and the translational version. With the theoretical background, the structural features of these devices in “Wuthering Heights” and its translational version are identified and described with in-depth analysis of linguistic features. In general, structural features of simile and repetition in the two novels are nearly the same. Therefore, the structural features of simile and repetition found in the novel Wuthering Heights remain in its Vietnamese translational version. However, because of the differences in the Western and Eastern cultures, the structural features as well as semantic features of simile and repetition in the original novel are faithfully translated into Vietnamese in the translated version, still keeping the same device and without keeping the same device. Furthermore, the study also suggests some implications in learning a foreign language or translating a literary word as well as for further studies are put forward.